PPARγ Expression and Function in Mycobacterial Infection: Roles in Lipid Metabolism, Immunity, and Bacterial Killing - Patricia E. Almeida; Alan Brito Carneiro; Adriana R. Silva; Patricia T. Bozza (PPAR Research)
Tuberculosis continues to be a global health threat, with drug resistance and HIV coinfection presenting challenges for its control. Mycobacterium tuberculosis, the etiological agent of tuberculosis, is a highly adapted pathogen that has evolved different strategies to subvert the immune and metabolic responses of host cells. Although the significance of peroxisome proliferator-activated receptor gamma (PPARγ) activation by mycobacteria is not fully understood, recent findings are beginning to uncover a critical role for PPARγ during mycobacterial infection. Here, we will review the molecular mechanisms that regulate PPARγ expression and function during mycobacterial infection. Current evidence indicates that mycobacterial infection causes a time-dependent increase in PPARγ expression through mechanisms that involve pattern recognition receptor activation. Mycobacterial triggered increased PPARγ expression and activation lead to increased lipid droplet formation and downmodulation of macrophage response, suggesting that PPARγ expression might aid the mycobacteria in circumventing the host response acting as an escape mechanism. Indeed, inhibition of PPARγ enhances mycobacterial killing capacity of macrophages, suggesting a role of PPARγ in favoring the establishment of chronic infection. Collectively, PPARγ is emerging as a regulator of tuberculosis pathogenesis and an attractive target for the development of adjunctive tuberculosis therapies.